A Daya Terima Dan Kandungan Fitokimia ( Antioksidan, Serat, Indeks Glikemik, Dan Vitamin C) Pada Minuman Sehat Mar'ke Billar Sebagai Alternatif Pencegahan Obesitas: Daya Terima dan Uji Kandungan Fitokimia (Antioksidan, Serat, Indeks Glikemik, dan Vitamin C) pada Minuman Sehat Mar'ke Bilar sebagai Alternatif Pencegahan Obesitas - Siahaan, Ginta; Tarigan, Novriani; Siregar, Ice Ratnalela (Universitas Airlangga, 2023)
Background: Obesity is a multifactorial disease that occurs due to excessive storage of fat tissues. The World Health Organization (WHO) states that obesity and overweight are risk factors for the fifth cause of death in the world. A nutritional status monitoring initiated by the Directorate of Community Nutrition of the Indonesian Ministry of Health in 2018 showed that the percentage of the obese adult population aged >18 years was 28.5%, and the 2018 Basic Health Research found 21.8% of the population. Obesity can be prevented by consuming fruits and tubers that are high in fiber, vitamin C, antioxidants, and low glycemic index (GI) value. Objectives: This study aims to determine the acceptability and phytochemical test of antioxidant, fiber, glycemic index, and vitamin C of Mar'ke Bilar, a healthy drink. Methods: Experimental research was conducted using a complete randomized design (CRD) consisting of three treatments and two repetitions. Antioxidant, vitamin C, fiber, and GI levels were assessed afterward. Results: The organoleptic test results show the highest acceptability obtained in formulation 2 consisting of 30 ml passion fruit, 50 ml persimmon, 50 ml purple sweet potato, and 70 ml water. Formulation 2 contained 39.73 mg/ml antioxidant, 4.0 g fiber, 62% GI, and 56.81 mg vitamin C. This means that Mar'ke Bilar can be used as an alternative to obesity prevention. Conclusions: Formulation 2 is the selected formulation in which the drink is purplish pink, not too thick, watery, refreshingly sweet, and slightly sour with a total antioxidant content of 39.73 mg/ml, 4.0 g of fiber, GI of 62%, and vitamin C of 56.81 mg.